Le Mecklembourg–Poméranie-Occidentale, un littoral touristique entre réhabilitation et ancrage dans une aire allemande et baltique - Lauriane Létocart (M@ppemonde)
The cradle of German seaside tourism, the coastline of Mecklenburg-Western Pomerania, has been a complex area since reunification. Managing military and GDR heritages while facing increased competition has challenged the state’s development of seaside tourism. Tourism officials are in search of new strategies in order to better position themselves within the Baltic area.